Penerapan Model Pembelajaran Kooperatif Untuk Meningkatkan Keaktifan Mahasiswa Pada Mata Kuliah Kewarganegaraan - Astutik, Nur Fithria Wiji (JURNAL EKONOMI, MANAJEMEN, BISNIS, DAN SOSIAL (EMBISS), 2024)
Students are the next generation and "agents of change" who must continue the struggle that their predecessors have achieved to maintain independence. The independence that is meant is that students have a spirit of responsibility to always ensure that the Indonesian state remains strong and intact, and students can continue the leadership milestones of their predecessors to move Indonesia towards becoming a more advanced and better country from year to year. This hope can be realized by lecturers applying the cooperative learning model as an alternative solution in increasing student activity when participating in learning activities in citizenship courses in the Civics Study Program. Qualitative research will be combined with classroom action research to maximize research results. It is proven by the lecturer's innovation by implementing the STAD type cooperative learning model that students experience increased activity, starting from the pre-cycle by 25%, then cycle I by 55%, and cycle II by 85% of students being declared complete, where students are again active in the learning process.